Contribution of Heptose Metabolites and the cag Pathogenicity Island to the Activation of Monocytes/Macrophages by Helicobacter pylori - Faass, Larissa; Stein, Saskia C.; Hauke, Martina; Gapp, Madeleine; Albanese, Manuel; Josenhans, Christine (Frontiers in Immunology, 2021)
The human gastric pathogen Helicobacter pylori activates human epithelial cells by a particular combination of mechanisms, including NOD1 and ALPK1-TIFA activation. These mechanisms are characterized by a strong participation of the bacterial cag pathogenicity island, which forms a typeIV secretion system (CagT4SS) that enables the bacteria to transport proteins and diverse bacterial metabolites, including DNA, glycans and cell wall components, into human host cells. Building on previous findings, we sought to determine the contribution of lipopolysaccharide inner core heptose metabolites (ADP-heptose) in the activation of human phagocytic cells by H. pylori. Using human monocyte/macrophage-like Thp-1 cells and human primary monocytes and macrophages, we were able to determine that a substantial part of early phagocytic cell activation, including NF-B activation and IL-8 production, by live H. pylori is triggered by bacterial heptose metabolites. This effect was very pronounced in Thp-1 cells exposed to bacterial purified lysates or pure ADP-heptose, in the absence of other bacterial MAMPs, and was signficantly reduced upon TIFA knock-down. Pure ADP-heptose on its own was able to strongly activate Thp-1 cells and human primary monocytes/macrophages. Comprehensive transcriptome analysis of Thp-1 cells coincubated with live H. pylori or pure ADP-heptose confirmed a signature of ADP-heptose-dependent transcript activation in monocyte/macrophages. Bacterial enzyme-treated lysates (ETL) and pure ADP-heptose-dependent activation differentiated monocytes into macrophages of predominantly M1 type. In Thp-1 cells, the active CagT4SS was less required for the heptose-induced proinflammatory response than in epithelial cells, while active heptose biosynthesis or pure ADP-heptose were required and sufficient for their early innate response and NF-B activation. The present data suggest that early activation and maturation of incoming and resident phagocytic cells (monocytes, macrophages) in the H. pylori-colonized stomach strongly depend on bacterial LPS inner core heptose metabolites, also with a significant contribution of an active CagT4SS.